2021
DOI: 10.18632/aging.203293
|View full text |Cite
|
Sign up to set email alerts
|

The deubiquitinase OTUD3 stabilizes ACTN4 to drive growth and metastasis of hepatocellular carcinoma

Abstract: OTU domain-containing protein 3 (OTUD3), a deubiquitinating enzyme, has been shown to participate in progression of multiple malignancies. The accurate function of OTUD3 in hepatocellular carcinoma (HCC) progression remains elusive. We found that OTUD3 was significantly overexpressed in HCC, and higher OTUD3 expression was correlated with larger tumor size, more distant metastasis, and worse TNM stage. A series of gain-and loss-of-function assays were also performed to examine the oncogenic function of OTUD3 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…For instance, the ‘writers’ METTL3 is upregulated and governs in invasion/migration through MMP2 in melanoma [ 35 ]. As for the ‘erasers’, ALKBH5 promotes the progression of uveal melanoma [ 36 ] and sensitizes tumors to cancer immunotherapy in melanoma [ 37 ]. Also, knockdown of FTO markedly improves cell sensitivity to interferon (IFN)-γ and anti-PD-1 therapeutics in melanoma, which suggested a promising anticarcinogenic therapy [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the ‘writers’ METTL3 is upregulated and governs in invasion/migration through MMP2 in melanoma [ 35 ]. As for the ‘erasers’, ALKBH5 promotes the progression of uveal melanoma [ 36 ] and sensitizes tumors to cancer immunotherapy in melanoma [ 37 ]. Also, knockdown of FTO markedly improves cell sensitivity to interferon (IFN)-γ and anti-PD-1 therapeutics in melanoma, which suggested a promising anticarcinogenic therapy [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…USP11 promotes colorectal cancer growth and metastasis by stabilizing PPP1CA, activating the ERK/MAPK pathway, and insulin-like growth factor 2 mRNA binding protein 3 (IGF2BP3) signaling ( 151 ), and interacting with nuclear factor 90 (NF90) to promote HCC proliferation and metastasis ( 152 ). OTU domain-containing protein 3 (OTUD3), a deubiquitinating enzyme, also promotes HCC proliferation and metastasis by regulating α-actinin 4 (ACTN4) ( 153 ). The deubiquitinating enzyme PSMD14 directly interacts with Snail and stabilizes it to promote cell migration and tumor metastasis of esophageal squamous cell carcinoma ( 154 ).…”
Section: Epigenetic In Tumor Progression and Metastasismentioning
confidence: 99%
“…A growing number of reports suggest the role of OTUD3 in human cancers, such as breast cancer as well as lung cancer ( 35 , 46 ). Studies have demonstrated that OTUD3 is expressed in high amounts in HCC tissues and is associated with a poor prognosis in HCC patients ( 47 ). α-Actin 4 (ACTN4) is called an actin-binding protein and belongs to a family of actin-binding proteins.…”
Section: Ovarian Tumor Protease Otumentioning
confidence: 99%
“…α-Actin 4 (ACTN4) is called an actin-binding protein and belongs to a family of actin-binding proteins. OTUD3 can affect the expression of α-actin 4 (ACTN4) at the protein level and promote the proliferation, invasion, and metastasis of HCC by stabilizing ACTN4 by deubiquitination ( 47 ).…”
Section: Ovarian Tumor Protease Otumentioning
confidence: 99%